تأثير الصراع في اليمن على مجلس التعاون لدول الخليج العربية (2012-2017) - غريب, علي (جامعة الوادي.University eloued, 2017)
يعتبر التكامل الحل الأمثل للدول لمواجهة التحديات والعقبات التي تقف كحاجز في طريق بناء مستقبلها ونموها, خاصة في حالة وجود صراعات تهدد امنها واستقرارها, ولقد حاولت دول مجلس التعاون لدول الخليج العربية أن تحقق صيغة من صيغ التكامل من خلال التعاون فيما بينها ومحاولة توجهها وابرزها التحدي الأمني الذي هو الدافع الابرز لتكاملها.. غير أن الصراع في اليمن كشف عن صعوبة تعامل دول المجلس التعاون مع الصرعات الإقليمية في ظل تكتل التكامل المتبع، الأمر الذي يعجل من ضرورة اتحادها وقد بنيت هذه الدراسة على الإشكالية التالية: ما مدى تأثير الصراع في اليمن على مجلس التعاون لدول الخليج العربية؟It is the integration of the best solution for countries to meet the challenges and obstacles that stand as a barrier by building its future growth, especially in the case of conflicts threaten its security and stability, and I have tried the Gulf Cooperation Council (GCC), to achieve a formula of Dag integration through cooperation among them, and try its orientation towards unity , what helped to withstand the challenges they face, most notably the security challenge, which is the motivation most prominent integration ... but the conflict in Yemen revealed the difficulty of dealing GCC countries with regional conflicts under block followed integration, which the \ j accelerates the necessity of their union was built this study on persons The following mechanism
م.س..ح.ر17